Bigger Pictures for Innovation Creating Solutions, Managing Enterprises, and Influencing Policies. - Rouse, William B. (Milton : Productivity Press, 2023)
This book comprises a set of stories about being an engineer for many decades and the lessons the author learned from research and practice. These lessons focus on people and organizations, often enabled by technology.
Indiana Alzheimer's Care -- Penn Transition Care for Elderly Patients -- Enterprise Models -- New York City Health Ecosystem -- Population Health -- Technology Innovation -- Summary -- Health Advisor -- Education -- Computational Model -- Scenario Projections -- Technology Investments -- Online Education -- Interactive Technologies -- Knowledge Management -- Process Improvement -- Impacts on Ecosystem -- Impacts on Competitiveness -- STEM Talent Pipeline -- Conclusions -- Epilogue -- Further Reading -- Chapter 9 Modeling and Visualization -- Prologue -- Introduction -- Phenomena -- Definitions
Description based upon print version of record.
Historical Perspectives
OCLC-licensed vendor bibliographic record.
Keywords: Decision making; Strategic planning; Organizational change; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning